Moersch-Woltman Syndrome - An Uncommon Conundrum - Dos Santos, Vitorino M.; C. Modesto, Laura; C. Modesto, Julia (International Journal of Medical Students, 2024)
Recently, this Journal published an interesting case study about the Moersch-Woltman syndrome that affected a middle-aged female, who had not an early diagnosis of this uncommon condition and was longtime submitted to polypharmacy without any improvement of the relentless course of this disease. The authors commented on the importance of a high index of suspicion to get an early correct diagnosis and prompt effective management that is indispensable to result in the best outcomes. The additional short comments on novel literature data aim to emphasize the exemplifying role of reported cases, mainly by enhancing the awareness of non-specialists and primary healthcare workers.